2015
DOI: 10.3109/14767058.2015.1031739
|View full text |Cite
|
Sign up to set email alerts
|

Changes in T-cell phenotype and cytokines profile in maternal blood, cord blood and colostrum of diabetic mothers

Abstract: The results obtained suggest that maternal hyperglycemia modifies the phenotypes of T cells and cytokines profile in maternal, cord blood and colostrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
4
22
1
Order By: Relevance
“…In this study, we report that CB retains a lower proportion of CD3 + T cells but the same proportion of CD4 + T cells with maternal PB. This finding was inconsistent with previous report which demonstrated that CD3 + and CD4 + T cells were increased in CB compared to PB [44]. More interestingly, our findings showed that CD3 + and CD4 + T cells in RPB were significantly lower than those in PB, which suggested that T cell-related immunity was suppressed at the maternal-fetal junction at the time of parturition.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we report that CB retains a lower proportion of CD3 + T cells but the same proportion of CD4 + T cells with maternal PB. This finding was inconsistent with previous report which demonstrated that CD3 + and CD4 + T cells were increased in CB compared to PB [44]. More interestingly, our findings showed that CD3 + and CD4 + T cells in RPB were significantly lower than those in PB, which suggested that T cell-related immunity was suppressed at the maternal-fetal junction at the time of parturition.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to participating in several metabolic functions, cytokines may assume modulatory, stimulatory or even inhibitory endocrine functions [15]. They act at very low concentrations, binding to specific cell membrane receptors and activating a cascade of metabolic reactions [16,17]. They may be useful markers for assessing the effects of physical exercise on the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the biochemical and immunological changes of HC related to maternal overweight and obesity. It is known that this condition is associated with low grade inflammation, confirmed by an increase in serum cytokines and inflammatory markers in maternal and fetal blood [ 14 , 17 , 65 , 66 ] and can be potentially aggravated during pregnancy, representing a disease predisposing factor both for the mother and also for the fetus (and later in life) [ 14 , 67 , 68 , 69 ].…”
Section: Proteomicsmentioning
confidence: 99%
“…It is known that breastfeeding can protect from the onset of obesity, diabetes and cardiovascular disease. Furthermore, human colostrum (HC) seems to have a peculiar role in newborn support and plays a protective role against allergic and chronic diseases, in addition to long-term benefits such as a reduction in systo-diastolic pressure and total cholesterol, decreased risk of Type 2 Diabetes Mellitus (DM2), overweight and obesity [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%